6-7x=6x-9x+2

Simple and best practice solution for 6-7x=6x-9x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-7x=6x-9x+2 equation:


Simplifying
6 + -7x = 6x + -9x + 2

Reorder the terms:
6 + -7x = 2 + 6x + -9x

Combine like terms: 6x + -9x = -3x
6 + -7x = 2 + -3x

Solving
6 + -7x = 2 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
6 + -7x + 3x = 2 + -3x + 3x

Combine like terms: -7x + 3x = -4x
6 + -4x = 2 + -3x + 3x

Combine like terms: -3x + 3x = 0
6 + -4x = 2 + 0
6 + -4x = 2

Add '-6' to each side of the equation.
6 + -6 + -4x = 2 + -6

Combine like terms: 6 + -6 = 0
0 + -4x = 2 + -6
-4x = 2 + -6

Combine like terms: 2 + -6 = -4
-4x = -4

Divide each side by '-4'.
x = 1

Simplifying
x = 1

See similar equations:

| 3(x-5)=3x+6 | | 3-6y=19y-14 | | (8/3-4)/(7/6+1) | | 34/6=12x+1/3 | | 8.58n+3.55=-2.91n+4.81 | | 6/5/1-7/4 | | 102=12x+1 | | 5/6/(1-7/4) | | 3(3x-5)+4x+2=-104 | | 2/3(D+6)-4D | | -19-3+25-41=-4-3m-8+4m | | (1/2-5/4)/(6/5-5/3) | | 96=80x-16x^2 | | 2(-2x-2)+5x+1=-6 | | x=4y+12 | | 4n^2-5n+5=0 | | 7(x-(2))-(4x)=10 | | 50/5(2) | | 3/4=w+2/3 | | 5z-3z=6 | | -m/3=16 | | .166666666d+.666666666=.25(d+-2) | | 1/5x-4/9=8/45 | | 3/4(12y+8)-3(4y+7)=0 | | -3(2x+2)-3x+3=87 | | -5t^2+100t+20=0 | | v^2-v+45=0 | | v^2-v+45=0 | | (1+4/5)/(1-8/5) | | y=-7x-28 | | 3(3x-4)+5x-5=81 | | h/2x=4.3 |

Equations solver categories